Where we do stand on integrity? - Abd Razak, Dzulkifli (2007)
Three years ago, the prime minister introduced the idea of a National Integrity Plan, to promote ethical practices. It was a commendable effort as the prime minister has been championing ethics and integrity as one of his main platforms for change for a better Malaysia. The people support it as a bold initiative that many felt was overdue. Added to this is the concept of Islam Hadhari which boosts integrity in all walks of life. The National Fatwa Council had given its unanimous support as the way forward to make Malaysia more dynamic and progressive. Islam Hadhari principles are consistent with the tenets of many other belief systems.